RANDOMIZED COMPARISON OF TWO APPROACHES TO WARFARIN DOSAGE IN CARDIOVASCULAR HOSPITAL SECTION - L. N. Mishchenko; O. V. Averkov; I. G. Gordeev; E. E. Tyulkina; E. P. Pavlikova; N. N. Levchuk; I. G. Pletnikova (Российский кардиологический журнал)
Aim. To compare two approaches to warfarin dosage formulation: the standard and with the clinical algorithm.Material and methods. As an approach to warfarin dosage, we have used the method that included clinical properties of the patients. Into the group of the studied approach (intervention group), we randomized 31 person, into the standard approach group (controls) — 29 persons with a variety of indications for vitamin K antagonists treatment. Target diapason of International Normalized Ratio (INR) for all the patients was 2,0 to 3,0.Results. A stable target INR in both groups was reached during hospitalization just in a small part of the patients: 19,4% in intervention group and 17,2% in controls. The patients from intervention group reached stable INR by 6,8 days in average, that is almost two times faster than controls, who had their target INR by 12,4 day in average (p<0,05). Part of the INR values higher than 4,0 in intervention group was 3,6%, in control group — 18,2% (p<0,05). Thromboembolic events (strokes, pulmonary embolism repeats) has not developed in both groups. There was one bleeding episode in each of the groups.Conclusion. Opportunities for targeting INR, not dependent on dosing regimen, are quite restricted in inpatient settings. The patients having reached target INR, usage of clinical algorithm of warfarin dosage helped to achieve these values much faster than in standard approach. Prevalence of excessive hypocoagulation while using the algorithm was lesser than in standard group. Key words: ;